The addition of β-Hydroxy β-Methylbutyrate (HMB) to creatine monohydrate supplementation does not improve anthropometric and performance maintenance across a collegiate rugby season - Gerald T. Mangine; Trisha A. VanDusseldorp; Garrett M. Hester; Jennifer M. Julian; Yuri Feito (Taylor & Francis Group, 2020)
Background Muscular damage sustained while playing rugby may hinder performance across a season. β-Hydroxy β-Methylbutyrate (HMB) may help attenuate muscle damage and maintain lean mass and performance. This study sought to determine the effect of combining HMB with creatine monohydrate supplementation on measures of stress and muscle damage, body composition, strength and sprinting kinetics throughout a rugby season. Methods This double-blind, cross-over investigation recruited 16 male collegiate rugby players to provide resting blood samples and complete assessments of body composition, strength and sprinting performance prior to their fall season (PREFALL). After testing, the athletes were matched for fat-free mass and assigned to consume one of two supplementation regimens for 6 weeks: 5 g HMB + 5 g creatine per day (HMB-Cr: 20.9 ± 1.1 years; 177 ± 2 cm; 88.4 ± 4.9 kg) or 5 g creatine + 5 g placebo per day (Cr: 21.4 ± 2.1 years; 179 ± 2 cm; 88.3 ± 4.9 kg). After 6 weeks (POSTFALL), PREFALL testing was repeated in 13 of the original 16 athletes before a 10-wk wash-out period. Athletes who returned for the spring season (n = 8) repeated all fall-season procedures and testing prior to (PRESPRING) and following (POSTSPRING) their 6-wk spring season, except they were assigned to the opposite supplementation regimen. Results Linear mixed models with repeated measures revealed group x time interactions (p <  0.05) for observed for several measures but did not consistently and positively favor one group. During the fall season, knee extensor peak torque was reduced by 40.7 ± 28.1 Nm (p = 0.035) for HMB-Cr but remained consistent for Cr, and no group differences or changes were noted in the spring. In the spring, greater knee flexor rate of torque development (~ 149 Nm·sec− 1, p = 0.003) and impulse (~ 4.5 Nm·sec, p = 0.022) were observed in Cr at PRESPRING but not at POSTSPRING. Although significant interactions were found for cortisol concentrations, vastus lateralis pennation angle, and sprinting force, post-hoc analysis only revealed differences between fall and spring seasons. No other differences were observed. Conclusions The combination of HMB and creatine monohydrate supplementation does not provide a greater ergogenic benefit compared to creatine monohydrate supplementation alone. Body composition, strength, and sprinting ability did not change across the season with creatine monohydrate supplementation.